VALUE OF A FARM ANIMAL WELFARE PROGRAM IN BURSA-TURKEY - Serkan GURLUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to present the value of a farm animal welfare (FAW) program that is not compulsory in South Marmara Region of Turkey. It is based on the face-to-face survey results administered in rural areas of Bursa City. The study measures the willingness to accept of producers for changing FAW levels in regards to sheep and goat husbandry. Contingent valuation technique is employed in the statistical analysis. Three different FAW levels were identified for valuation as "base" level, "better" level, and the "best" level. The best level was the most stringent FAW program. The current study suggests a protocol with WTA(P) nomenclature to resolve complexity issues in FAW studies by investigating producers rather than consumers. FAW programs’ value were calculated as130.3 million United States Dollars (USD) for base scenario. The figures were 166.2 million USD/Year and 175 million USD/Year for “better” and “best” FAW conditions, respectively. The results show that FAW programs have strong public opinion and non-market value.